2013
DOI: 10.1016/j.cyto.2012.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Signals from fat after injury: Plasma adipokines and ghrelin concentrations in the severely burned

Abstract: Introduction Hypermetabolism is universal in the severely burned and is characterized by catabolism of lean mass and body fat with associated insulin resistance. Adipokines are likely to play a role in these changes but have not been identified to date in burn patients. Methods From a single burn ICU, 17 burn patients with an expected stay >14 days were studied. Study period began within 14 days of admission. Over seven days, plasma samples were collected for measurement of leptin, adiponectin, resistin, ghr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
(50 reference statements)
2
17
0
Order By: Relevance
“…Both leptin and adiponectin have recently been shown to be reduced in critically ill patients and associated with stress related parameters [15,49,50]. We have recently seen similar changes in adipokines in patients with severe burns [16]. These adipokines have been suggested to play important roles in tissue inflammation; however, a role in critically ill patients has yet to be elucidated [51-53].…”
Section: Discussionmentioning
confidence: 97%
“…Both leptin and adiponectin have recently been shown to be reduced in critically ill patients and associated with stress related parameters [15,49,50]. We have recently seen similar changes in adipokines in patients with severe burns [16]. These adipokines have been suggested to play important roles in tissue inflammation; however, a role in critically ill patients has yet to be elucidated [51-53].…”
Section: Discussionmentioning
confidence: 97%
“…In our study, there were statistically signi cant positive correlations between the resistin concentrations of the multiple trauma patients and the corresponding SIRS and MOF scores. Wade et al found a signi cant positive correlation between the resistin plasma concentrations and the multiple organ dysfunction score in patients with burn trauma [44]. In addition, Sundén-Cullberg et al demonstrated a statistically signi cant correlation between the resistin concentrations and the SOFA score in sepsis patients [45].…”
Section: Resistinmentioning
confidence: 99%
“…When the patient has no difficulty tolerating oral feeding, soft, bland foods are recommended for the first meal and chewing foods thoroughly is encouraged. Patients are often easily satiated and therefore have minimal solid food intake, but they are extremely thirsty, which aids in meeting calorie goals by drinking 8-24 supplement drinks per day [42]. Water, Gatorade®, Kool-Aid®, fruit juices, and sodas are not calorically dense enough to adequately support nutrition in the hypermetabolic state.…”
Section: Oral Nutritionmentioning
confidence: 99%